Tujuan Hidup: Prediktor dari Komitmen Berpacaran pada Emerging Adulthood - Harmoko, Kezia Kevina; Hosea, Felicia Angie; Widjaja, Richelleen; Tandra, Jeanie Sindayani; Poniman, Nicholas Oswald; Yuliawati, Livia; Wardhani, Putri Ayu Puspieta; Yohanes, Hioe Ricky (Psychopreneur Journal, 2025)
Finding identity and life purpose is one of emerging adulthood’s developmental tasks. It can help them be in a committed relationship, which is also their developmental task. However, the Friends With Benefits phenomenon in emerging adulthood in Indonesia indicates a lack of dating commitment, whereas it is important to commit and thus study predictors promoting commitment. Therefore, this research aims to find whether life purpose can be a predictor of dating commitment in emerging adulthood in Indonesia. Participants are 305 Indonesians aged 18-25 years old who are in a dating relationship. They completed online questionnaires consisting of the Indonesian version of the Claremont Purpose Scale and Sternberg Triangular Love Scale’s commitment scale. Based on the simple linear regression test, life purpose positively predicts dating commitment with goal-directedness being the highest predictor. This shows that life purpose has a positive impact on the dating commitment of emerging adulthood in Indonesia.